Pendidikan Humanisme dalam Proses Pendidikan Islam - Dwi Kartika Susanti; Muhammad Guntur Alting (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
According to humanist education, the most crucial component of education is students' cognitive or intellectual growth, which is equally as significant as their affective growth. Clearly, the most significant component of education in humanistic education is the recognition that intellectual or cognitive growth is just as vital as affective development. Human growth, cultural values, and human values are obviously given a lot of weight in humanistic education. Humanistic education aims to produce trustworthy, self-respecting, democratized, imaginative unbiased, and reasonable people who can excel at time management and adjust to changing conditions. Along with being decent citizens who belong to their families, societies, and communities, these people should The humanistic approach to teaching allows students to think and act in accordance with the goals of Islam and humanity. It does this by teaching them about Islam from an interdisciplinary perspective. Teachers can enhance their students' critical thinking abilities and help them develop their talents, attitudes, and skills to the fullest extent possible through humanist education.